Understanding Sexual Minority Adolescents - Christine Regan; Kate Fogarty (EDIS)
FCS-9237, a 5-page fact sheet by Christine Regan and Kate Fogarty, is one in a series of discussions on understanding teen sexuality. It helps adults who work with youth understand what sexual orientation is, the challenges faced by LGBT adolescents, and the stages of homosexual identity development. Includes resource lists and references. Published by the UF Department of Family Youth and Community Sciences, August 2006.